Faktor - Faktor Penyebab Fluktuasi Harga Smartphone Pada Pasar Oligopoli (Studi Kasus Pasar Peterongan Jombang) - Amarudin, Amin Awal; Fadilah, Risma Nur; Ardiansyah, Muhammad; Arrasyid, Abraham; Puspitasari, Della (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2025)
The smartphone market, dominated by several major brands, reflects the characteristics of an oligopolistic market with intense competition and dynamic price fluctuations. This study aims to analyze the factors contribubuting to smartphone price fluctuations in Peterongan Market, Jombang, as well as to understand how interactions among market participants (sellers, distributors, and manufacturers) influence these dynamics. The research utilizes a qualitative descriptive method, with primary data collected through in-depth interviews with four counter owners and 45 consumers, along with direct observation at the location. Secondary data were obtained from reports by the International Data Corporation (IDC) and supporting literature related to smartphone price trends. The findings reveal that price fluctuations are influenced by a combination of internal factors, such as technological innovation and marketing strategies, as well as external factors, such as imbalances in supply and demand, government fiscal policies, and global economic conditions. Interactions among market participants play a crucial role, with manufacturers setting base prices, distributors adjusting to local market conditions, and sellers implementing promotional strategies to attract consumers. The impact of these fluctuations affects price-sensitive consumers, sellers who must adjust their sales strategies, and manufacturers who are required to maintain competitiveness through product innovation. This study provides valuable insights for market participants in managing price dynamics and helps consumers gain a better understanding of the market